DNA minicircles capable of forming a variety of non-canonical structural motifs - Trizna, Lukáš; Olajoš, Jakub; Víglaský, Viktor (Frontiers in Chemistry, 2024)
Although more than 10% of the human genome has the potential to fold into non-B DNA, the formation of non-canonical structural motifs as part of long dsDNA chains are usually considered as unfavorable from a thermodynamic point of view. However, recent experiments have confirmed that non-canonical motifs do exist and are non-randomly distributed in genomic DNA. This distribution is highly dependent not only on the DNA sequence but also on various other factors such as environmental conditions, DNA topology and the expression of specific cellular factors in different cell types. In this study, we describe a new strategy used in the preparation of DNA minicircles containing different non-canonical motifs which arise as a result of imperfect base pairing between complementary strands. The approach exploits the fact that imperfections in the pairing of complementary strands thermodynamically weaken the dsDNA structure at the expense of enhancing the formation of non-canonical motifs. In this study, a completely different concept of stable integration of a non-canonical motif into dsDNA is presented. Our approach allows the integration of various types of non-canonical motifs into the dsDNA structure such as hairpin, cruciform, G-quadruplex and i-motif forms but also combinations of these forms. Small DNA minicircles have recently become the subject of considerable interest in both fundamental research and in terms of their potential therapeutic applications.